Wireless mobile ultrasonic detector - Abd Razak, Muhammad Ab. Basith (2008)
Nowadays wireless data transmission has become famous method of sending data. There are several types of wireless data transmission such as Frequency Modulation (FM), Amplitude Modulation (AM), wireless data transmission, Bluetooth, satellite communication, wireless broadband and others. All the wireless data transmission used to transmit data inside space platforms. Wireless data transmission method are increasing practically and used everywhere such as video and audio data in television, security data, computer data likes client server, turn on light or in security systems. Because of that, this project is creating to improve the method where the design involves hardware and software. The microcontroller unit MC68HC11A1 is programmed using assembly language and connected to Visual Basic software using serial port DB9. In this project, the wireless system consists of transmitter and receiver module using Radio Frequency (RF) where it is connected to ultrasonic sensor. When the sensor detects the obstacle, it will send the data and receives by the receiver at microcontroller unit. From the microcontroller, the data will display at PC using Visual Basic software. Wireless FM transmitter and receiver module with operating frequency at 433.92 MHz was chose in order to achieve the objective of the wireless communication.